2018
DOI: 10.1080/14397595.2018.1481727
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with decreasing serum 25(OH)D among Japanese patients with rheumatoid arthritis: Results from the IORRA cohort study

Abstract: Female gender, younger age, JHAQ-DI, tender joint counts, and disuse of bisphosphonates and/or active vitamin D appear to be associated with a decrease in serum 25(OH)D in Japanese patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The IORRA cohort was established in October 2000 as a single, institute-based, large, observational cohort of Japanese patients with RA at the Institute of Rheumatology, Tokyo Women’s Medical University. Details regarding the purpose and methodology of this study have been reported previously [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. Over 139 publications have described various characteristics of Japanese patients with RA from this large cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IORRA cohort was established in October 2000 as a single, institute-based, large, observational cohort of Japanese patients with RA at the Institute of Rheumatology, Tokyo Women’s Medical University. Details regarding the purpose and methodology of this study have been reported previously [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. Over 139 publications have described various characteristics of Japanese patients with RA from this large cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have reported various clinical characteristics of osteoporosis in Japanese patients with RA by way of utilizing data from our Institute of Rheumatology Rheumatoid Arthritis (IORRA) cohort study [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. For patients with RA, the prevention of fractures is important to the maintenance of their quality of life (QoL), thus their osteoporosis requires appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%